Formal methods for industrial critical systems : 23rd International Conference, FMICS 2018, Maynooth, Ireland, September 3-4, 2018, Proceedings /: 23rd International Conference, FMICS 2018, Maynooth, Ireland, September 3-4, 2018, Proceedings. (2018) - Unknown
No abstract available